2009
DOI: 10.1073/pnas.0811421106
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the impact of the Andean uplift on Neotropical plant evolution

Abstract: Recent phylogenetic studies have revealed the major role played by the uplift of the Andes in the extraordinary diversification of the Neotropical flora. These studies, however, have typically considered the Andean uplift as a single, time-limited event fostering the evolution of highland elements. This contrasts with geological reconstructions indicating that the uplift occurred in discrete periods from west to east and that it affected different regions at different times. We introduce an approach for integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
534
1
27

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(582 citation statements)
references
References 55 publications
20
534
1
27
Order By: Relevance
“…This hypothesis is also congruent with the biogeographical history of Central American and Andean Polystichum proposed by Driscoll and Barrington (2007) as well as McHenry and Barrington (2014), who suggested that the Neotropical clade has a northern origin, and that the Andean Polystichum lineage originated from a boreotropical Mexican ancestor. A similar biogeographical pattern has been proposed for other boreotropical fern (e.g., Nephrolepis: Hennequin et al, 2010;Diplazium: Wei et al, 2015), as well as angiosperm taxa (Fabaceae: Lavin et al, 2001; Malpighiaceae: Davis et al, 2002;Sapotaceae: Smedmark and Anderberg, 2007; Rubiaceae: Antonelli et al, 2009;Annonaceae: Erkens et al, 2009). Here the boreotropical scenario is supported by several Northern Hemisphere fossils dating back to the early Paleogene indicating an ancient occurrence in regions viewed as former boreotropical provinces.…”
Section: Early Diverging Clades In Polystichoid Ferns: Evidence For Bsupporting
confidence: 69%
See 2 more Smart Citations
“…This hypothesis is also congruent with the biogeographical history of Central American and Andean Polystichum proposed by Driscoll and Barrington (2007) as well as McHenry and Barrington (2014), who suggested that the Neotropical clade has a northern origin, and that the Andean Polystichum lineage originated from a boreotropical Mexican ancestor. A similar biogeographical pattern has been proposed for other boreotropical fern (e.g., Nephrolepis: Hennequin et al, 2010;Diplazium: Wei et al, 2015), as well as angiosperm taxa (Fabaceae: Lavin et al, 2001; Malpighiaceae: Davis et al, 2002;Sapotaceae: Smedmark and Anderberg, 2007; Rubiaceae: Antonelli et al, 2009;Annonaceae: Erkens et al, 2009). Here the boreotropical scenario is supported by several Northern Hemisphere fossils dating back to the early Paleogene indicating an ancient occurrence in regions viewed as former boreotropical provinces.…”
Section: Early Diverging Clades In Polystichoid Ferns: Evidence For Bsupporting
confidence: 69%
“…Ching (Polypodiaceae), in which pulses of diversification coincide with the uplift of QTP and climate change Wang et al, 2012). Whereas recent investigations have highlighted the key role of the Andean orogeny in the diversification of several South American clades (e.g., Hughes and Eastwood, 2006;Antonelli et al, 2009;Hoorn et al, 2010), the precise impact of the QTP uplift on the evolution of Eastern Asian biota remains poorly understood (Favre et al, 2014) and the diversification pattern of a only a few taxa such as Saussurea DC. (Wang et al, 2009), Lilium L. (Gao et al, 2013) and Rhodiola L. (Zhang et al, 2014) has been investigated.…”
Section: Recent Transoceanic Disjunctions: Evidence For Lddmentioning
confidence: 99%
See 1 more Smart Citation
“…He proposed that the H-D Movement should be recognized as an independent phase in the Q-T Plateau orogeny (Chen, 1992(Chen, , 1996. Previous authors have suggested that the timing and rate of biological speciation may provide insight into the timing of orogenic events (e.g., Antonelli et al, 2009;Picard et al, 2008;Stigall Rode and Lieberman, 2005;Che et al, 2010). For example, a historical biogeographic study of the family Rubiaceae was used to test the alternative hypotheses that the Andes Mountains rose continuously or in stages of uplift and quiescence (Antonelli et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These estuarine environments of varying salinity provide pathways for evolutionary habitat transition of many marine-derived organisms [6 -8]. Marine incursions may have also functioned as impenetrable dispersal barriers for terrestrial species, fragmenting their previously continuous distribution ranges and leading to vicariant speciation [9]. Because its division and coalescence effects often produce bursts of diversification, incursion is considered to be one of the most productive 'species pumps' [2].…”
Section: Introductionmentioning
confidence: 99%